Changes in the world distribution of output-per-worker 1960 - 98: How a standard decomposition tells an unorthodox story - Paul Beaudry; Fabrice Collard; David Alan Green (Institute for Fiscal Studies (IFS), 2004)
Why have some countries done so much better than others over the recent past? In order to shed new light on this issue, this paper provides a decomposition of the change in the distribution of output-per-worker across countries over the period 1960-98. The main finding of the paper is that most of the change in shape of the world distribution of income between 1960-1998 can be accounted for by a very substantial and previously unrecognized change in the parameters driving the growth process. In particular, we show that the role of capital deepening forces - that is the role of investment rates and population growth in affecting output - increased dramatically over the period 1978-98 versus 1960-78, and that this increase can account for almost all the observed changes in the world distribution. In contrast, we do not find any significant effects coming through non-linear convergence mechanisms or increased importance of education; both of which have played prominent roles in recent discussion of economic performance. Our results therefore highlight that the period 1978-98 was particularly advantageous to countries which strongly favored capital accumulation and hence suggests that research aimed at understanding recent differences in economic performances across countries needs to focus on explaining why the social returns to physical capital accumulation where abnormally high over the period 1978-98.
Keywords: O33; O41; 330; World Income Distribution; Cross–Country Growth; Human and Physical Capital Accumulation; Labor Force growth; Arbeitsproduktivität; Einkommensverteilung; Vergleich; Welt